2005
DOI: 10.1300/j077v23n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Man to Man and Side by Side, They Cope with Prostate Cancer

Abstract: Prostate cancer affects men and their loved ones; consequently, survivors and their wives can gain from social support throughout the illness experience. After observing meetings of a support group for prostate cancer survivors and their partners, the authors used the constant comparison method to draw conclusions about the types of support generated in the men's and women's divisions of the group. The authors concluded that both divisions served as sites of information but not as scenes of practical assistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 24 publications
4
66
0
3
Order By: Relevance
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…The majority of the studies were conducted in the USA (n = 13 studies) 101,110,113,114,123,[128][129][130]136,208,213,217 and the UK (n = 11), 99,100,102,108,112,115,116,128,209,214,216 with the remainder in Australia (n = 5), 109,111,118,210,212 Canada (n = 5) 107,117,120,125,211 and the following: Denmark, 207 France, 218 South Africa 215 and Sweden…”
Section: Countrymentioning
confidence: 99%
See 2 more Smart Citations
“…This raises questions about whether there might be improvements needed to existing psychosexual services and how best to facilitate 4 men's access to health care if they experience problems [22,23]. Empirical evidence supports a popular belief that men encounter difficulties disclosing psychological difficulties during consultations [8,[24][25][26]. Health care seeking for mental health difficulties has been described as being particularly challenging to masculinities [27,28], which may exacerbate problems in identifying and addressing patients' psychosexual needs.…”
Section: Introductionmentioning
confidence: 99%